The Integration of Fiqh and Science: The Pork Element in the Medical Fatwa's of the Indonesian Ulema Council - Abubakar, Ali; Harahap, Muhammad Ridwan; Habibi, Muhammad; Nurdin, Abidin; Gayo, Ahyar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Although the integration of religion and science has been widely examined across disciplines, it remains relatively underexplored within the field of fiqh (Islamic jurisprudence), particularly in relation to medical issues. This study therefore addresses a substantial gap in the existing literature. Here, case of integration in the fatwa's issued by the Indonesian Ulema Council (Majelis Ulama Indonesia / MUI) was examined. These fatwas addressed vaccines that were considered haram (forbidden) since they contained or came into contact with pork-derived elements, except in cases of emergency. On the contrary, the East Java branch of the MUI permitted their use based on the concept of complete chemical transformation (istihālah tammah). To explore this issue, the study posed three research questions: (1) How are elements related to pork positioned within MUI fatwas? 2) How does the authority of ulama affect the positioning of pork-derived elements in MUI fatwa's? and (3) How is the integration model of fiqh and science articulated in MUI fatwa's? The first question was examined through content analysis of existing MUI fatwas, the second through analysis of interview data from Muslim intellectuals in Jakarta, East Java, West Sumatra, and Aceh, and the third through an integrated analysis of interview data and fatwa documents using the theory of authority. The findings thus indicate that the MUI adopts an integrative approach to science and fiqh in issuing fatwa's. However, the role of science tends to remain largely confirmatory and has yet to exert a more substantive influence. In this regard, the East Java MUI has taken a more ‘open’ approach, moving beyond the established mainstream of fiqh while still operating within the framework of classical ulama authority